Maintaing strong literacy programs - Tatlonghari, Melchor A. (The RAP Journal, 2004)
This paper challenges schoolas and school systems to build strong literacy programs. Discussed are the characteristics of a strong literacy program, namerly 1) based on a comprehensive view of literacy, 2) possesses sound and valid assessment framework and procedures , 3)reseach-based, 4) clearly defines and identifies the roles of all stakeholders of the program, and 5) flexible. Embedded in the discussion are ways to achieve these characteristics based on sound theory.